2019
DOI: 10.56093/ijans.v89i9.93774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of reproductive traits of Sahiwal cattle

Abstract: Data on first lactation reproduction traits of Sahiwal cattle maintained at an organized herd of the institute over a period of 29 years (1988–2016) were analyzed in the present study. Effect of various genetic and non–genetic factors on first lactation reproduction traits in addition to their genetic control was assessed by using mixed model least–square analysis. The overall least–square means for first lactation reproduction traits, viz. age at first service (AFS), age at first calving (AFC), number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…Posterior mean of permanent environmental (above diagonal) and residual correlations (below diagonal) along with posterior standard deviation for different performance traits in Sahiwal cattle LMY, LL, PY, DPY, DP GP, CFI, DO and CI as 1935.13 kg, 2022.49 kg, 277.90 days, 12.62 kg, 43.90 days, 137.13 days, 286.82 days, 85.62 days, 134.22 days and 425.42 days, respectively in Sahiwal cattle.Means observed for different traits were in concordance with the results of earlier studies(Ratwan et al 2018a(Ratwan et al , 2019a(Ratwan et al , 2020b(Ratwan et al , 2021. Period of calving had signi cant (p < 0.01) in uence on all considered traits except DPY and GP.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Posterior mean of permanent environmental (above diagonal) and residual correlations (below diagonal) along with posterior standard deviation for different performance traits in Sahiwal cattle LMY, LL, PY, DPY, DP GP, CFI, DO and CI as 1935.13 kg, 2022.49 kg, 277.90 days, 12.62 kg, 43.90 days, 137.13 days, 286.82 days, 85.62 days, 134.22 days and 425.42 days, respectively in Sahiwal cattle.Means observed for different traits were in concordance with the results of earlier studies(Ratwan et al 2018a(Ratwan et al , 2019a(Ratwan et al , 2020b(Ratwan et al , 2021. Period of calving had signi cant (p < 0.01) in uence on all considered traits except DPY and GP.…”
supporting
confidence: 90%
“…A multi-trait model includes all the information available on animals and thereby increases the precision of estimating genetic parameters (Pollak et al 1983). Earlier, researchers used maximum likelihood approaches in Sahiwal cattle to assess genetic parameters of performance traits (Rehman et al 2008;Ratwan et al 2018a;2019a;a). Additionally, researchers have estimated heritability, repeatability and genetic associations between production and fertility traits in dairy animals using Bayesian and restricted maximum likelihood methods (Kumar et al 2016;Ratwan et al 2018b;2019b;Worku et al 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [22], Ben et al [9] and Zhu et al [62] have reported similar heritability estimates in Holstein Friesian cattle. Ratwan et al [47] reported a higher estimate in Sahiwal and Lomole [36] reported a slightly higher estimate in Sahiwal cattle than the present study. Zhu et al [62] reported a lower estimate in Holstein Friesian cattle than in the presentstudy.…”
Section: Number Of Services Per Conception (Nspc)contrasting
confidence: 78%
“…Heritability estimate for the gestation period was found to be relatively low compared to production traits, indicating that genetic factors play a smaller role in determining the length of pregnancy.Management practices such as nutrition and health care may have a more substantial impact on the gestation period compared to genetic selection.The heritability estimate of the gestation period in the present study was in agreement with the reports of Al-Samarai et al [2], Das et al [13] and Kumar et al [27] in Holstein Friesian and crossbred cattle, respectively. Ratwan et al [47] also reported a similar estimate in Sahiwal cattle. Selvan et al [50], Lomole [36] and Ratwan et al [48] reported a lower estimate in Sahiwal cattle than the present study.…”
Section: Gestation Period (Gp)mentioning
confidence: 67%